Application of ESP32 as a Media for Learning Ozone Damage in the Form of IoT-Based Ultraviolet Index Readers - Nugroho Adi Pramono; Fauzan Ibnu Sofyan; Bertha Anggita Purwandani; Oktavia Ghaisyani (Journal of Disruptive Learning Innovation (JODLI), 2020)
Ultraviolet light is part of the electromagnetic waves from solar radiation. Excessive UV light can cause damage to human skin. High UV index caused by one of the damage to the ozone layer, therefore it is important we study the ozone damage in an area. On this occasion made learning media in the form of an IoT-based ultraviolet index reader. This tool uses ESP32 as a controller by adding several modules namely UV index sensor and wifi module. The existence of a wifi module makes it easy for us to send data and control ESP32 using the internet, therefore this tool is said to be based on the Internet of Things (IoT). With this tool we can compare the UV Index level in several regions simultaneously without being in that area. From the difference in index, we can study the level of UV radiation in each region in real time. Therefore we can study the comparison of ozone damage levels.